Anticancer and Anti-Neuroinflammatory Constituents Isolated from the Roots of Wasabia japonica - Jong Eel Park; Tae Hyun Lee; Song Lim Ham; Lalita Subedi; Seong Min Hong; Sun Yeou Kim; Sang Un Choi; Chung Sub Kim; Kang Ro Lee (MDPI AG, 2022)
Wasabi (Wasabia japonica (Miq.) Matsum.) is a pungent spice commonly consumed with sushi and sashimi. From the roots of this plant, a new 2-butenolide derivative (1) and 17 previously reported compounds (2-18) were isolated and structurally characterized. Their chemical structures were characterized based on the conventional NMR (1H and 13C, COSY, HSQC, and HMBC) and HRESIMS data analysis. All of these phytochemicals (1-18) were evaluated for their antiproliferative effects on the four human tumor cell lines (A549, SK-OV-3, SK-MEL-2, and MKN-1), for their inhibitory activity on nitric oxide (NO) production in lipopolysaccharide (LPS)-activated BV-2 microglia cells, and for their nerve growth factor (NGF)-releasing effect from C6 glioma cells. Among the isolated compounds, compound 15 showed powerful antiproliferative activities against A549 and SK-MEL-2 cell lines with IC50 values of 2.10 and 9.08 μM, respectively. Moreover, the new compound 1 exhibited moderate NO inhibition activity with IC50 value of 45.3 μM.